Successful treatment of mixed depth flame burns using enzymatic debridement with Nexobrid™ in a patient with aggressive systemic sclerosis (scleroderma). (January 2019) - Wickham, Neil; Alexander, K. Skaria; Fletcher, Anthony; O'Boyle, Ciaran
Introduction: Enzymatic debridement for mixed depth and full thickness burns is gaining recognition as an important technique available to the burns surgeon. Reductions in blood loss, the need for autologous skin grafting and the number of wounds requiring surgical excision are among the benefits of this evolving treatment modality. We present a case of successful treatment using enzymatic debridement of mixed depth flame burns in a young patient with systemic sclerosis (scleroderma). Methods: A 24-year-old man with rapidly progressive limited cutaneous systemic sclerosis suffered approximately 6% mixed depth flame burns to the right leg including areas of likely deep partial thickness burn totalling approximately 2% total body surface area (TBSA). Enzymatic debridement using Nexobrid™ was performed under spinal anaesthesia in accordance with unit protocol. Pain was well controlled and at 4 h the Nexobrid™ was removed and replaced with saline-soaked gauze initially then simple dressings. After liaison with Rheumatology, he was also started on iloprost infusions over five days. He was discharged home on day 9 and completely healed by day 31. Scarring was minimal, the skin was soft and full, and pain-free range of movement of the right knee was maintained. Discussion and Conclusion: This case demonstrates the safety and effectiveness of enzymatic debridement of mixed depth burns in a patient with very compromised wound healing. Enzymatic debridement combined with iloprost infusion provided maximum preservation of viable dermis. The authors recommend that this treatment strategy is considered in similar cases. Lay summary: This case report describes a patient with a flame burn injury to the leg who was successfully treated using an enzyme-based topical formulation. This product is increasingly being used to treat burn injuries of varying severity. The patient had a pre-existing medical condition (scleroderma) which means that they have a significantly impaired ability to heal wounds following injury. The patient was also treated with a drug (iloporost) which can help wound healing in patients with this medical condition. The topical enzyme used in this case is likely to have preserved all the viable tissue in the injured leg. This combined with the drug treatment (iloprost) helped heal the burn successfully with no complications and possibly eliminated the need for surgery.